The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11249-020-01298-6
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of Phase Change in Highly Loaded Frictional Contacts

Abstract: Highly loaded lubricated contacts may present a friction plateau on which the friction force becomes independent from the sliding velocity. Although this phenomenon has been known for a long-time, its physical origin remains poorly known. The present paper aims at giving further insight on the physical mechanisms triggering the friction plateau. The study specifically focuses on the influence of pressure on the physical state of the lubricant. An uncoupled experimental approach (rheology, tribology, spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…14,[24][25][26][27] Measurements of viscosity and limiting shear stress have been conducted using high-pressure rheometers. [28][29][30][31] Shear localisation in accordance with the appearance of the limiting shear stress has also been investigated. [32][33][34][35][36][37] It has been recognised that traction is generated within the lubricated area, while a film is formed by the lubricant flow based on a Newtonian fluid at the entrance.…”
Section: Introductionmentioning
confidence: 99%
“…14,[24][25][26][27] Measurements of viscosity and limiting shear stress have been conducted using high-pressure rheometers. [28][29][30][31] Shear localisation in accordance with the appearance of the limiting shear stress has also been investigated. [32][33][34][35][36][37] It has been recognised that traction is generated within the lubricated area, while a film is formed by the lubricant flow based on a Newtonian fluid at the entrance.…”
Section: Introductionmentioning
confidence: 99%
“…However, many studies have shown that when the lambda ratio is less than three, e.g., about one, the lubrication regime has already been in the full film EHL for the studied The LSS is usually believed to be a kind of shear localization such as a wall slip [7,8] or a plug flow [9,10]. Some other work suggested that LSS may be related to the thermal effects and glass transition of lubricants [11][12][13][14]. Over the past decades, molecular dynamics (MD) simulations have been used to simulate the rheological properties of fluids under conditions of high pressure and high shear [15][16][17].…”
Section: Introductionmentioning
confidence: 99%